Follicular Helper T (TFH) Cell Targeting by TLR8 Signaling For Improving HBsAg-Specific B Cell Response In Chronic Hepatitis B Patients - Ayithan, Natarajan; Tang, Lydia; Tan, Susanna K.; Chen, Diana; Wallin, Jeffrey J.; Fletcher, Simon P.; Kottilil, Shyam; Poonia, Bhawna (Frontiers in Immunology, 2021)
Identifying signaling pathways that induce B cell response can aid functional cure strategies for chronic hepatitis B infection (CHB). TLR8 activation with ssRNA was shown to enhance follicular helper T cell (TFH) function leading to improved B cell responses in vitro. We investigated whether this mechanism can rescue an exhausted immune response in CHB infection. Effect of TLR8 agonism on supporting cytokines and TFH and B cells were evaluated using ex vivo and in vitro assays. The ability of an oral TLR8 agonist to promote TFH and B cell response was tested in samples from phase 1b clinical trial. TLR8 agonism induced TFH polarizing cytokine IL-12 in monocytes. Treatment of peripheral blood mononuclear cells (PBMCs) from CHB patients with TLR8 agonists induced cytokine IL-21 by TFH cells with enhanced IL-21+BCL-6+ and ICOS+BCL-6+ co-expression. Mechanistically, incubation of isolated naïve CD4+ T cells with TLR8 triggered monocytes resulted in their differentiation into IL-21+ICOS+BCl-6+ TFH in an IL-12 dependent manner. Furthermore, co-culture of these IL-21 producing TFH with autologous naïve B cells led to enhanced memory (CD19+CD27+) and plasma B cell generation (CD19+CD27++CD38+) and IgG production. Importantly, in TFH from CHB patients treated with an oral TLR8 agonist, HBsAg-specific BCL-6, ICOS, IL-21 and CD40L expression and rescue of defective activation induced marker (AIM) response along with partial restoration of HBsAg-specific B cell ELISPOT response was evident. TLR8 agonism can thus enhance HBV-specific B cell responses in CHB patients by improving monocyte-mediated TFH function and may play a role in achieving HBV functional cure.